2022
DOI: 10.3390/vetsci10010001
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Fiber Immunohistochemical Panel Discriminates between Nerve Sheath and Perivascular Wall Tumors

Abstract: Benign and malignant nerve sheath tumors (NST) pose a major challenge in routine diagnostic anatomic pathology because of shared histomorphological features with other soft-tissue tumors (STT). As a result, NST are often diagnosed as STT, a broad category that encompasses various entities including perivascular wall tumors (PWT) and that represents approximately 15% of all skin tumors in dogs. Immunohistochemistry (IHC) can assist the identification of histologic subtypes of STT. This IHC pilot study applies v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Similar to the published cases, vimentin (2/2 cases), laminin (5/5 cases), and claudin-1(1/1 case) frequently labeled neoplastic perineurial cells. Previously, Sisó et al ( 14 ) has shown positive expression of S-100, GFAP, Periaxin, and Sox-10 in canine perineuriomas.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Similar to the published cases, vimentin (2/2 cases), laminin (5/5 cases), and claudin-1(1/1 case) frequently labeled neoplastic perineurial cells. Previously, Sisó et al ( 14 ) has shown positive expression of S-100, GFAP, Periaxin, and Sox-10 in canine perineuriomas.…”
Section: Discussionmentioning
confidence: 88%
“…The intermediate filament protein GFAP, primarily expressed in glial cells, exhibits variable expression in benign nerve sheath tumors ( 14 ). No GFAP expression was detected in the presented cases 1–3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S-100 and Leu-7 are positive in immunohistochemistry. [ 12 , 13 ] Clinical signs and symptoms may vary depending on the anatomical location of HN tumors. Most patients present with painless masses, while some may present with pain and tenderness.…”
Section: Discussionmentioning
confidence: 99%